2022
DOI: 10.3389/fgene.2022.931797
|View full text |Cite
|
Sign up to set email alerts
|

An integrative analysis of the lncRNA-miRNA-mRNA competitive endogenous RNA network reveals potential mechanisms in the murine hair follicle cycle

Abstract: Alopecia is a common progressive disorder associated with abnormalities of the hair follicle cycle. Hair follicles undergo cyclic phases of hair growth (anagen), regression (catagen), and rest (telogen), which are precisely regulated by various mechanisms. However, the specific mechanism associated with hair follicle cycling, which includes noncoding RNAs and regulation of competitive endogenous RNA (ceRNA) network, is still unclear. We obtained data from publicly available databases and performed real-time qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The HF cycle is a tightly regulated process, and emerging evidence suggests that lncRNAs play an essential role in its regulation [11, 15, 16]. We observed that HFSCARC expression was higher during the anagen phase of HF cycle compared to the telogen phase.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The HF cycle is a tightly regulated process, and emerging evidence suggests that lncRNAs play an essential role in its regulation [11, 15, 16]. We observed that HFSCARC expression was higher during the anagen phase of HF cycle compared to the telogen phase.…”
Section: Discussionmentioning
confidence: 78%
“…Long noncoding RNAs (lncRNAs) transcript are more than 200 nucleotides and do not encode proteins. Multiple lines of evidences showed that lncRNAs have been demonstrated to involve in HF cycle [11,12]. LncRNAs play multiple roles, including transcription regulation, chromatin remodeling, mRNA splicing, and editing, and involvement in proliferation, differentiation, apoptosis and other biological processes of HFSC [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-149-5p could induce hair follicle stem cell differentiation in goats by promoting the expression of β-catenin [30]. In addition, many studies also revealed the regulation relationship of miRNA-lncRNA-mRNA in hair follicle development [31][32][33]. APA is a kind of posttranscriptional process that could change the binding site of miRNA and mRNA [34].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy emerged as one of the augmented signaling pathways in a Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis of 105 downregulated mRNAs transitioning from the anagen to the catagen phase. 65 Additionally, a comprehensive evaluation of autophagic activity in the HF cycle on mice's dorsal skin revealed an elevation of autophagy in anagen, a diminution in catagen, and stable low levels during telogen. 66 Active autophagic flux was predominantly observed in hair matrix keratinocytes and dermal adipocytes encircling the HFs.…”
Section: Autophagy and Alopecia-related Diseasesmentioning
confidence: 99%